The Prevalence of Photoconjunctivitis and Conjunctival Lesion among Fishermen in Jazan in Saudi Arabia: And the Association of Its Risk Factors - A, Ahmed (International Journal of Innovative Research in Medical Science, 2018)
Attributable to the nature of their occupation, fishermen are consistently exposed to the hazardous UV radiation which not only affects the skin but also the eye. The objective of this study is to determine the prevalence of photoconjunctivits and conjunctival lesions among fishermen in Jazan and the association with socio-demographic background and occupational history. This study employed a cross-sectional study design conducted in the Jazan region of Saudi Arabia among 511 fishermen. Data collection using a set of questionnaire was assisted by interviewer which is ensued by an eye examination. The prevalence of the photo conjunctivitis was found to be 4.3% and that of conjunctival lesions at 0.8%. An association was seen between the prevalence of photoconjunctivitis and conjunctival lesions to the exposure of sunlight.